Optimal control of pollutants with delayed stock accumulation - Ralph Winkler (ETH Zurich, CER-ETH - Center of Economic Research, 2008)
We study the optimal control of a pollutant that accumulates with a delay.We find that optimal paths are, in general, non-monotonic and oscillatory, but monotonic if the objective function is additively separable. Hence, using additively separable objective functions as an approximation to a general objective function may be a misspecification. With a numerical example we illustrate that an additively separable approximation performs considerably worse in delayed compared to instantaneous stock accumulation.
Keywords: Q50; C61; 330; additively separable objective; approximated objective; delayed optimal control; optimal pollution control; Umweltbelastung; Umweltschutz; Mathematische Optimierung; Kontrolltheorie; Umweltökonomik; Theorie